Analysis of the thin layer drying kinetic of brown lentil grains - Lens Culinaris (Research, Society and Development, 2021)
In this work, different thin layer drying profiles for brown lentil grains - Lens Culinaris at temperatures of 35, 45, 55 and 65 ºC, at a speed of 0.8 m/s and 25 % water content are analyzed. The objective is to analyze the drying kinetics of lentil grains, adjusting the parameters observed for temperatures of 35, 45, 55 and 65 °C, with an initial water content of 25 % wet basis, to different mathematical models, in addition to determining the thermodynamic properties (enthalpy, entropy and Gibbs free energy) for the process. The drying process of the grains was performed at the Laboratório de Armazenamento e Processamento de Produtos Agrícolas (LAPPA) of the Agricultural Engineering Department of the Federal University of Campina Grande – UFCG. The grains used in the study were acquired in the local market of Campina Grande – PB. Where the kinetic curves for different mathematical models were analyzed. Thus, it was possible to observe that the model with the best fit was the Cavalcanti Mata model.